Dark-Singular Straddled Optical Solitons for the Dispersive Concatenation Model with Power-Law of Self-Phase Modulation by Tanh-Coth Approach - Mohamad Jawad, Anwar Ja' afar; Biswas, Anjan; Yildirim, Yakup; Alshomrani, Ali Saleh (Contemporary Mathematics, 2024)
This paper recovers dark-singular straddled optical solitons for the dispersive concatenation model with power-law of self-phase modulation using the tanh-coth approach. The individual dark or singular solitons are not supported by the model for power-law unless this law collapses to Kerr law as proven with the usage of undetermined coefficients, earlier.